Usability testing for library websites : a hands-on guide - Norlin, Elaina; Winters, CM! (Chicago : American Library Association, 2002)
"Unless you're the librarian who set them up, online library services can be hard to navigate. In fact, many users give up in frustration without ever finding what they're looking for. As libraries increasingly use the Web to deliver both in-house and remote services online, it is critical that their sites be engaging, easy to navigate, and created with the end user - the library customer - in mind." "This soup-to-nuts guide will help beginners and experts alike determine in a systematic way how well their Web sites are performing for their customers."--Jacket.
Foundations of usability testing -- Web design guidelines -- Getting buy-in -- Preassessment and planning -- Preparing and evaluating the usability test -- Usability testing example.
Includes bibliographical references (pages 65-66) and index.
NLJCols20082021
Keywords: Library Web sites -- Testing; User interfaces (Computer systems) -- Testing; Web sites -- Design; Sites Web de biblioth eques -- Essais; Interfaces utilisateurs (Informatique) -- Essais; Sites Web -- Conception; User interfaces (Computer systems) -- Testing; Web sites -- Design; Website; Bewertung; Bibliothek; Gestaltung; Web-Seite; Websites; Bibliotheken; Gebruikersinterfaces; Gebruikersonderzoek; Library Web sites -- Testing; User interfaces (Computer systems) -- Testing; Web sites -- Design; Bibliothek